The Effect Of NPM, ROA, ROE, EPS And Per Ratio On The Stock Price Of Lq45 Companies Listed On The Indonesian Stock Exchange For The Period 2021-2023 - Nadia Puspitasari; Ahmad Soleh; Yudi Irawan Abi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
There are many companies listed on the Indonesia Stock Exchange (BEI), but there is a special classification for companies with the best financial performance. One of them is a company included in the LQ45 index group. The purpose of this study was to determine the effect of Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER) on stock prices. In this study, the data were analyzed using statistical methods. Data processing using the SPSS statistical program. The statistical test used to analyze the data is multiple linear regression analysis. The results showed that Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER) have an effect on stock prices in LQ45 companies for the period 2021-2023